Knowledge, Attitude and Practice (KAP) on haze among secondary school student in Hulu Langat, Selangor - Abdul Rahman, Haliza; Shamsul Bahari, Nur Hazami (Human Resource Management Academic Research Society, 2020)
Haze has become an annual occurrence in Malaysia that sets back years ago starting from 1980s until recently in September 2019. Most people are affected by haze, as its impacts can cause from light to severe reaction(s), especially to the vulnerable group such as children, elderly and pregnant women etc. Hence, it is very crucial to equipped this susceptible group with enough protection so that they are able to minimize the risk from the exposure of haze. However, before all else, their current level of knowledge, attitude and practice on haze issues should be known, in order to create the suitable preventive measure(s) for them. Hence, a study of the knowledge, attitude and practices on haze between secondary school students in Hulu Langat, Selangor was conducted. A cross-sectional study design was used to determine the knowledge, attitude and practices on haze between two groups, which were Form 3 students and Form 5 students from Sekolah Menengah Kebangsaan (SMK) Perimbun. A set of modified questionnaires was administrated, and a total of 318 respondents were involved. This is to determine their sociodemographic characteristic, knowledge about haze, attitude towards haze, and practice during haze. Furthermore, ‘Statistical Package for Social Sciences (SPSS) Version 22.0 was used to analysed the results. The results showed that the level of knowledge for Form 3 students and Form 5 students were moderate at 51 (81%) and 197 (77.3%) respectively. The level of attitude of Form 3 students and Form 5 students were again, moderate, at 44 (69.8%) and 190 (74.5%) respectively. Form 3 students and Form 5 students were also at a moderate level for practice during haze which were at 48 (76.2%) and 204 (80.0%) respectively. Furthermore, the results from Mann-Whitney U test indicates, that there was only a significant difference on the level of knowledge (z = -3.352, p = 0.001) between Form 3 students and Form 5 students. While there was no significant difference between level of attitude (z = -1.168, p = 0.243) and level of practice (z = -1.154, p = 0.248) among form 3 and form 5 students. Another Chi Square test was run and it reported that there was an association between attitude and practice (p=0.018, p<0.05). In conclusion, Form 3 students and Form 5 students were deemed to have moderate knowledge and attitude and good practice on haze. Hence, it is recommended to enhanced the knowledge of these students as it could direct them towards a better attitude and practice during haze, and this can be done by reviewing the Environmental Education (EE) taught in school syllabus.